PROTOTIPE SISTEM PENJERNIH UDARA DALAM RUANGAN - , RURI APRIDIAN; , Hidayat Nur Isnianto, ST. M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final project report will be elaborated on the design of a sistem indoor air purifier. These sistems purify the air by the level of concentration of CO in the air where if CO levels over 35 ppm (MQ7 sensor read) then the sistem will activate the ionizer and the buzzer until CO levels below 35ppm. Ionizer serves to reduce levels of CO in the air while the sound of a buzzer serves as an indicator. The sistem uses the Arduino Uno as its center. With this sistem is expected to clear the air in a closed room, especially indoors with low energy and prevent the negative impact caused by pollutants.